2016
DOI: 10.1002/arch.21349
|View full text |Cite
|
Sign up to set email alerts
|

BMDREDD REGULATES THE APOPTOSIS COORDINATING WITH BMDAXX, BMCIDE‐B, BMFADD, AND BMCREB IN BMN CELLS

Abstract: The apoptosis mechanisms in mammals were investigated relatively clearly. However, little is known about how apoptosis is achieved at a molecular level in silkworm cells. We cloned a caspase homologous gene named BmDredd (where Bm is Bombyx mori and Dredd is death-related ced-3/Nedd2-like caspase) in BmN cells from the ovary of Bm and analyzed its biological information. We constructed the N-terminal, C-terminal, and overexpression vector of BmDredd, respectively. Our results showed that the transcriptional ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It undergoes a dramatic degeneration after spinning (Matsuura, Morimoto, Nagata, & Tashiro, ). Recently, many studies have elucidated the mechanism from the mRNA levels, some important genes such as Bmatg , BmDredd , and BmEcR were also found regulating the degeneration of the silkgland (R. T. Chen et al, ; R. Chen et al ; Huang et al, ; Zhang et al, , ). Many studies have demonstrated that some mRNAs could induce apoptosis in silkworm cells, but this was not clear enough to reveal why larva‐specific tissues degenerate while others not during the metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It undergoes a dramatic degeneration after spinning (Matsuura, Morimoto, Nagata, & Tashiro, ). Recently, many studies have elucidated the mechanism from the mRNA levels, some important genes such as Bmatg , BmDredd , and BmEcR were also found regulating the degeneration of the silkgland (R. T. Chen et al, ; R. Chen et al ; Huang et al, ; Zhang et al, , ). Many studies have demonstrated that some mRNAs could induce apoptosis in silkworm cells, but this was not clear enough to reveal why larva‐specific tissues degenerate while others not during the metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…This process involves hormone regulated programmed cell death that is apoptosis (Matsui, Kakei, Iwami, & Sakurai, ). Recently, some apoptosis‐related genes have been investigated in the silkworm silk gland or in silkworm ovary cells (R. T. Chen et al, ; Huang et al, ; Yi et al, ; Zhang et al, ; Zhang, Zhao, Qiao, Pan, & Lu, ). However, except for the function of Bm Dredd in the silk gland (R. Chen et al, ), few papers reported the functions of inhibiting or inducing apoptosis on the individual level of the silkworm.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some evidence has showed that Bm Dredd functions importantly in apoptosis. Its expression level was elevated in actinmycin D induced Bm E cells [17] and in actinmycin D or ultraviolet induced Bm N cells [25]. In addition, overexpression of Bm Dredd caused the increase of caspase3/8-like protease activity in Bm N-SWU1 cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, caspase‐3‐like activity was increased in the silk gland by overexpression of BmDredd. Taken together, the results suggest that BmDredd plays a critical role in silk gland apoptosis (R. T. Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 77%